2005
DOI: 10.1242/jcs.02539
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin adhesion depends on a salt bridge at the N-terminus

Abstract: ErratumHarrison, O. J., Corps, E. M. and Kilshaw, P. J. (2005). Cadherin adhesion depends on a salt bridge at the N-terminus. J. Cell Sci. 118, 4123-4130.The e-press version of this article that was published on 23rd August 2005 contains two errors on p. 4128. In the legend to Fig. 6, the penultimate sentence should read: Aggregation was assessed by microscopy. In the right-hand column, paragraph 2, the last sentence should read: It is not known whether similar changes to the ␤A strand in cadherins would modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 42 publications
3
37
0
1
Order By: Relevance
“…It has been shown that strand-exchange during cadherin dimer formation depends on the formation of an intermolecular salt bridge between the N-terminal amino group and the side chain of Glu-89 (41). An equivalent glutamic acid is found at position 88 in T-cadherin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that strand-exchange during cadherin dimer formation depends on the formation of an intermolecular salt bridge between the N-terminal amino group and the side chain of Glu-89 (41). An equivalent glutamic acid is found at position 88 in T-cadherin.…”
Section: Resultsmentioning
confidence: 99%
“…3C and 4). Fourth, studies with N-cadherin highlighted the relevance of an intermolecular salt-bridge between the N-terminal positively charged amide group and the negatively charged carboxylate of Glu-89 for dimer formation (41). Based on the observed distances in the calculated Tcad1 structures, ionic interactions between the N-terminal amide and Asp-26 as well as Asp-28 occur more often than with Glu-88 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The salt bridge is also conserved in type II cadherins (Patel et al 2006). This salt bridge has been shown to play a key role in forming the stand swapped interface (Harrison et al 2005). However, many of the reported affinity measurements used bacterially produced proteins that contain extensions at their amino-termini.…”
Section: Unique Properties Of Strand-swap Bindingmentioning
confidence: 99%
“…It is more likely, however, that both dimers-the cadherin dimer detected in the NMR study and the unstable dimer detected in our work-correspond to the strand dimer. The instability of the strand dimer has been explained by competition between intramolecular and intermolecular docking of Trp156 in conjunction with the relatively low energy barrier for Trp156 exchange (Chen et al, 2005, Harrison et al, 2005. The high-energy barrier, which provides stability for the strand dimer, must be based on much more extensive swapping.…”
Section: Stable and Unstable Cadherin Dimers Are Similar In Structurementioning
confidence: 99%